Patient, target, device, and program selection for DBS in Parkinson’s disease: advancing toward precision care - Aparna Wagle Shukla; Manuel Bange; Muthuraman Muthuraman (npj Parkinson's Disease)
Abstract In Parkinson’s disease (PD), several key factors influence patient selection for deep brain stimulation (DBS) as they directly affect long-term outcomes. A comprehensive interdisciplinary assessment is the first step to evaluating risks, benefits, and establishing appropriate goals. Patient-defined symptom priorities play a critical role in selecting the brain target for DBS. The entry of multiple manufacturers of hardware has spurred a rapid acceleration of technological progress. While innovations in programming such as sensing-based physiology-guided programming have introduced the concept of delivering an optimal or “Goldilocks dose”, a precise, personalized therapy to address specific PD symptoms, image-guided programming acts like a “GPS,” enabling faster determination of dose parameters. Emerging tools such as adaptive and automated programming offer clinicians the potential to provide optimal, energy-efficient stimulation. This review, integrating both old and well-established knowledge and new insights, provides a comprehensive summary of the multidimensional aspects of patient selection, target-specific benefits, advancements in hardware technology, and innovative strategies that are either currently available or on the horizon for DBS programming.